Breasts and the city: an urban ethnography of infant feeding in public spaces within Cardiff, United Kingdom - Aimee Grant (BMC, 2021)
Abstract Background Internationally, women report challenges breastfeeding in public spaces. This study aimed to investigate the social-spatial aspects of public spaces in one UK city, Cardiff, in order to suggest possible barriers and facilitators to breastfeeding in public spaces. Methods The study observation location guide prioritised places that had been reported as hostile to breastfeeding or breastfeeding friendly in the existing literature. Data were collected between April and September 2018 at various times of day, in several areas of the city, and included transport (n = 4), transport hubs (n = 3), high streets (n = 4), cafes (n = 2), a large city centre shopping complex, comprising of three joined shopping malls and a large city centre department store containing a third café. Low inference field notes were written on an encrypted smart phone and expanded soon after. Data were analysed thematically using deductive codes based on the observation schedule. Additional inductive codes relating to places were added. Results Overall, public transport and the city centre were inhospitable environments for those who might need to breastfeed, and even more so for those who need to express breastmilk. The core barriers and facilitators across locations were the availability of appropriate seating coupled with either high privacy or politely unimposing strangers (civil inattention). The one variation to this model arose from the department store café, where civil inattention was not performed and there was low privacy, but breastfeeding occurred anyway. Conclusions This research highlights the physical and social barriers to breastfeeding within one urban city centre in the UK and its associated transport links. It is clear that there is an urgent need for change in urban city centres and public transport if countries are to meet their aims in relation to increasing breastfeeding rates. Interventions will need to be multifaceted, accounting for social norms relating to infant feeding as well as changes to the physical environment, policy and potentially legal change. Further research should be undertaken in other countries to examine the extent to which hostile environments exist, and if correcting these could facilitate breastfeeding and reduce gender-based violence.